2017
DOI: 10.1016/j.jpurol.2017.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 30-day emergency department bouncebacks after pediatric versus adult urologic surgery

Abstract: Summary Introduction More pediatric patients seem to present to the emergency department (ED) for non-urgent matters after urologic procedures than adult patients. Under new and expanding healthcare reform, pediatric urologists may be penalized for these visits. We compare our 30-day postoperative bounceback rates to the ED and the acuity of the concerns in these populations. Materials and methods All urology consults at our institution are maintained on a prospectively tracked database. We identified all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…These brief interventions are appropriate even in safety net institutions whose patients may disproportionately access mental health care in the ED. (ED return rates observed here are slightly higher than those reported previously 19,20 21 …”
Section: Discussioncontrasting
confidence: 80%
“…These brief interventions are appropriate even in safety net institutions whose patients may disproportionately access mental health care in the ED. (ED return rates observed here are slightly higher than those reported previously 19,20 21 …”
Section: Discussioncontrasting
confidence: 80%
“…Interestingly, only 20% of those presenting to the ER require admission, whereas the remainder were discharged home. Pediatric patients are less likely to come back to the ER after surgery in comparison with their adult counterparts; however, those who do are significantly more likely to require only reassurance in comparison with adults who are more likely to require hospital admission (Shepard & Wan, 2017). Chua et al (2018) recently showed fewer emergency department visits and parent phone calls after penile surgeries when parents had the opportunity to review an atlas of expected healing stages postoperatively.…”
Section: Discussionmentioning
confidence: 99%